Significant social networks of bariatric patients in the context of recurrence of obesity - d’Avila Scherer, Alessandra (2023)
The objective of this qualitative study was to characterize the functions of significant social networks of patients who experienced obesity recurrence after bariatric surgery. For data collection, semi-structured interviews and application of the Network Map were used. The analysis of the data of the 12 participants was based on Grounded Theory and was supported by the Atlas-ti software. Family members were the most mentioned people playing, predominantly the role of emotional support. Noteworthy were the functions of emotional support, cognitive guidance and material help offered by the health team, as well as unmet expectations of help. It is sustained that knowing the relational dimension that surrounds bariatric patients allows us to highlight resources to face challenging moments inherent to the postoperative period, such as the recurrence of obesity.